Surface-enhanced Raman scattering properties of multi-walled carbon nanotubes arrays-Ag nanoparticles. (April 2016) - Zhang, Jie; Zhang, Xiaolei; Chen, Simeng; Gong, Tiancheng; Zhu, Yong
Abstract: A three-dimensional (3D) surface-enhanced Raman scattering (SERS) substrate is fabricated by decorating multi-walled carbon nanotubes (MWNTs) arrays with silver nanoparticles (AgNPs) on silicon, via magnetron sputtering and annealing method. The MWNTs-AgNPs hybrids with 3D structure increase the coverage of plasmonic nanostructures. The effect of inter-particle and inter-tube coupling creates a multitude of hot spots, with a strong SERS effect. The structure of MWNTs-AgNPs hybrid material is confirmed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Furthermore, Raman scattering from MWNTs, which is significantly enhanced in such hybrids, is systematically investigated in all samples. Surface-enhanced Raman scattering property is proved using 4-mercaptobenzoic acid (4-MBA) as standard analyte and the detection concentration level is down to 10 −10  M. Additionally, the stability and recyclability of MWNTs-AgNPs substrates have been studied, positioning SERS mapping within an area of 10 × 10 μm 2 is carried out to investigate the uniformity; time-course SERS mapping is performed to study the influence induced by molecule solution evaporation process. Finally, finite-difference time-domain (FDTD) method is utilized to simulate E-field distribution of the hybrid structures with multilayer AgNPs decorated on MWNTs. The results show a Raman scattering enhancement factor (EF) of 10 7 .